Development and Validation of the Short Version of the Reflux Symptom Score: Reflux Symptom Score–12. (January 2021) - Lechien, Jerome R.; Bobin, Francois; Rodriguez, Alexandra; Dequanter, Didier; Muls, Vinciane; Huet, Kathy; Harmegnies, Bernard; Crevier-Buchman, Lise; Hans, Stéphane; Saussez, Sven; Carroll, Thomas L.
Objective: To develop and validate a short version of the Reflux Symptom Score—the 12-question Reflux Symptom Score–12 (RSS-12)—for patients with laryngopharyngeal reflux disease (LPR). Study Design: Prospective study. Setting: Multicenter academic hospitals. Methods: Patients with LPR diagnosed via multichannel intraluminal impedance pH monitoring were enrolled from 3 European hospitals. Healthy individuals completed the study. Individuals completed the Reflux Symptom Score, Reflux Symptom Index (RSI), and Voice Handicap Index (VHI) at baseline and 3 months posttreatment. The Reflux Symptom Score was completed twice within a 7-day period to assess test-retest reliability. Cronbach's α was used for assessing internal consistency. The RSS-12 was developed and validity assessed through a comparison of the RSS-12, RSI, and VHI. Responsiveness to change was evaluated through the pre- to posttreatment evolution of the RSS-12 total score. Receiver operating characteristic analysis was used to determine the RSS-12 threshold that is suggestive of LPR. Results: The RSS-12 was characterized by high test-retest reliability ( r s = 0.956) and adequate internal consistency reliability (α = 0.739). The RSS-12 was significantly correlated with the RSI ( r s = 0.845), suggesting high external validity. The RSS-12 total and item scores were significantly higher in patients with LPR as compared with healthy individuals ( P = .001), supporting high internal validity. RSS-12, VHI, and RSI significantly improved throughout treatment. Regarding the receiver operating characteristic curve, an RSS-12 score >11 is suggestive of LPR, exhibiting a sensitivity of 94.5% and a specificity of 86.2%. Conclusion: The RSS-12 is a shorter, reliable, and valid self-administered patient-reported outcome measure questionnaire that can be used in the outpatient setting to suggest and monitor LPR.